Left ventricular adaptation after atrial septal defect closure assessed by increased concentrations of N-terminal pro-brain natriuretic peptide and cardiac magnetic resonance imaging in adult patients. Issue 5 (10th October 2005) - Weber, M; Dill, T; Deetjen, A; Neumann, T; Ekinci, O; Hansel, J; Elsaesser, A; Mitrovic, V; Hamm, C
Abstract : Objective: To determine in an observational study whether N-terminal pro-brain natriuretic peptide (NT-proBNP) is raised in patients with an atrial septal defect (ASD) and whether concentrations change after interventional closure. Methods: 12 patients (6 men, mean (SD) age 44.4 (18.6) years) with a moderate sized ASD type II (23.3 (4.5) mm, pulmonary to systemic flow ratio 2.1 (0.68)) were investigated. In all patients a magnetic resonance imaging (MRI) study was performed and NT-proBNP was assessed at baseline and early (9 (13) days) and late (138 (64) days) after intervention. Results: Concentrations of NT-proBNP were found to be within the normal range at baseline (median 87 pg/ml, interquartile range 65–181 pg/ml) but increased early after the interventional closure (315 pg/ml, 133–384 pg/ml, p = 0.005 versus baseline). The increase of NT-proBNP was associated with an increase in left ventricular dimensions as assessed by MRI (left ventricular end diastolic volume 104 (27) ml to 118 (27) ml, p = 0.003). Late after ASD closure NT-proBNP returned to baseline concentrations (102 pg/ml, 82–188 pg/ml, p = 0.004 versus early follow up). Conclusion: These findings suggest the presence of transitory haemodynamic stress during adaptation of the left ventricle after ASD closure, which may contribute to the understanding of the pathological mechanism of acute heart failure and delayed improvement of exercise capacity after ASD closure.